Analyzing Government Financial Performance as a Basis for Sustainable Development. Case Study on The Government of Klaten - Rahmawati Riantisari; Alfiati Nurrokhmini; Buya Al Ghazali (Komunitas Dosen Indonesia, 2025)
Financial ratio analysis in financial statements is useful for evaluating the effectiveness of the regional autonomy system. This study is a descriptive quantitative research. The research subject is the Klaten Regency Government, while the object of research is the Realization Report and the Regional Revenue and Expenditure Budget for the 2019-2022 period. Based on the analysis of the financial performance of the Klaten Regency government during the 2019-2022 budget period, it can be seen that the effectiveness ratio is very high, however, there are several indicators that show imbalances in financial management. One of them is the low activity ratio, which shows that more expenditure is allocated for operations than for capital investment. In addition, the very low independence ratio is also a concern, indicating that dependence on external resources is very high. To overcome this problem, concrete steps need to be taken including revenue diversification, improving financial management, spending efficiency, infrastructure development, human resources and strengthening the supervisory system in an effort to improve financial performance and sustainable development in Klaten Regency. The implications of the research highlight the need for budget policy reformulation and the strengthening of PAD management to enhance regional financial independence.